(x+2)(x^2-2x+4)-x(x-3)(x+3)=xКак решить, срочно!

0 голосов
36 просмотров

(x+2)(x^2-2x+4)-x(x-3)(x+3)=xКак решить, срочно!


Алгебра (41 баллов) | 36 просмотров
Дан 1 ответ
0 голосов

(x+2)(x^2-2x+4)-x(x-3)(x+3)=x

1. Используя (a + b)(a^2 - ab + b^2) = a^3 + b^3 получаем:

x^3 + 8 - x (x - 3) (x + 3) = x  

2. Используя (a  - b) (a + b) = a^2 - b^2 получаем:

x^3 + 8 - x (x^2 - 9) = x

3. Раскрываем скобки:

x^3 + 8 - x^3 + 9x = x

4. Сокращаем:

8 + 9x = x

5. Переносим неизвестное  влево:

9x - x = - 8

8x = -8

Ответ: x= -1

(50 баллов)